Metabolic activity diffusion imaging (MADI): II. Noninvasive, high‐resolution human brain mapping of sodium pump flux and cell metrics. (10th July 2022) - Springer, Charles S.; Baker, Eric M.; Li, Xin; Moloney, Brendan; Pike, Martin M.; Wilson, Gregory J.; Anderson, Valerie C.; Sammi, Manoj K.; Garzotto, Mark G.; Kopp, Ryan P.; Coakley, Fergus V.; Rooney, William D.; et al.
Abstract : We introduce a new 1 H2 O magnetic resonance approach: metabolic activity diffusion imaging (MADI). Numerical diffusion‐weighted imaging decay simulations characterized by the mean cellular water efflux (unidirectional) rate constant (kio ), mean cell volume (V), and cell number density (ρ ) are produced from Monte Carlo random walks in virtual stochastically sized/shaped cell ensembles. Because of active steady‐state trans‐membrane water cycling (AWC), kio reflects the cytolemmal Na +, K + ATPase (NKA) homeostatic cellular metabolic rate ( c MRNKA ). A digital 3D "library" contains thousands of simulated single diffusion‐encoded (SDE) decays. Library entries match well with disparate, animal, and human experimental SDE decays. The V and ρ values are consistent with estimates from pertinent in vitro cytometric and ex vivo histopathological literature: in vivo V and ρ values were previously unavailable. The library allows noniterative pixel‐by‐pixel experimental SDE decay library matchings that can be used to advantage. They yield proof‐of‐concept MADI parametric mappings of the awake, resting human brain. These reflect the tissue morphology seen in conventional MRI. While V is larger in gray matter (GM) than in white matter (WM), the reverse is true for ρ . Many brain structures have kio values too large for current, invasive methods. For example, the median WM kio is 22s −1 ; likely reflecting mostly exchange within myelin. The kio V product map displays brain tissue c MRNKA variation. The GM activity correlates, quantitatively and qualitatively, with the analogous resting‐state brain 18 FDG‐PET tissue glucose consumption rate ( t MRglucose ) map; but noninvasively, with higher spatial resolution, and no pharmacokinetic requirement. The cortex, thalamus, putamen, and caudate exhibit elevated metabolic activity. MADI accuracy and precision are assessed. The results are contextualized with literature overall homeostatic brain glucose consumption and ATP production/consumption measures. The MADI/PET results suggest different GM and WM metabolic pathways. Preliminary human prostate results are also presented. Abstract : The first noninvasive, homeostatic sodium pump activity image in the awake, resting human brain, driving active trans‐membrane water cycling (nmol[H2 Oi ]cycled/s/cell) (b). The high activity in the cortex, thalamus, putamen, and caudate correlates quantitatively (a) and qualitatively (c) with 18 FDG‐PET measured glucose consumption, but with higher resolution and no pharmacokinetic requirement.